How do Islamic banks manage earnings? Application of various measurement models in the Iranian Islamic banking system - Mahdi Ghaemi Asl; Mohammad Ghasemi Doudkanlou (ISRA International Journal of Islamic Finance, 2022)
Purpose - This study aims to identify and compare the measurement models of earnings management (EM) appropriate to the Iranian Islamic banking system. The importance of reported profit figures has motivated business executives, who also perform financial reporting, to manipulate these figures. These measures are referred to as "earnings management," which negatively influence the quality of reported earnings and financial statements' reliability. Design/methodology/approach - In this study, four methods, namely, Jones (1991), modified Jones (Dechow et al., 1995), Kasznik (1999) and Kothari et al. (2005), were used to measure the EM index in 25 Iranian Islamic banks (IBs) registered with the Tehran Stock Exchange and/or the Central Bank of Iran. The study covered the period 2005-2020. Following the aforementioned methods, this research implemented templates that were repeatedly tested in subsequent studies using accruals to discover EM. Findings - The results show that the Kasznik (1999) model is the preferred and compatible model with the Iranian Islamic banking system's accrual behaviour due to the consistency of the measurement coefficients with theoretical and previous research findings. Therefore, total accruals, including discretionary accruals and non-discretionary accruals, have the most correspondence with (1) property, machinery and equipment; (2) the change in cash flow from operating activities; and (3) the difference of change in revenue (ΔREV) and change in net receivable accounts (ΔREC). Originality/value - This is the first investigation in the Iranian Islamic banking system. The research contributes to the Iranian Islamic banking system literature on the implements of EM, which could be appealed to in the context of developing countries like Iran. Finally, this study highlights the different EM capabilities in Islamic banking systems similar to the Iranian banking arrangement.
Keywords: 330; Accounting earnings; Accruals; Earnings management; Iranian Islamic banking system